A Comparative Study of Tuberculosis Diseases in Diyala Province in 2010 and 2015 - Raghad Ibrahim (Journal of Global Pharma Technology, 2018)
Tuberculosis (TB) is one of the concern worldwide public health threats. A retrospective study conducted during the period (2016/11/14) until (2017/4/7) to comparative the incidence of tuberculosis disease in Diyala province between 2010 and 2015 years, the study-included number of patients with the chest and respiratory infections visited the central treatments of tuberculosis infections in Diyala. The patients included males and females with   ages from (20-90) years, they had been done X-ray chest and laboratory tests, including: examination of the septum with Ziehl–Neelsen testand (E.S.R).Examination had been identified a positive cases of tuberculosis among them, the number of patients infection with TB in (2010) were (147) cases from (1429) and (405) cases from (5772) patients   in (2015). The study showed that tuberculosis infections were  decline in 2015 to 7%  compares with  2010 to10.3%  .The results showed that (44.89%) of male and 55.1% in female  with TB infections in 2010. Also 47.90% of males  and 52.09% of females infected with TB in 2015 , the high rate of infection among age group  (31-50) in 2010, and (51-70 years) in 2015  , while the age group (71-90years) are showed the lowest ratio  were infected with TB infections for both 2010 and 2015. The results  appeared urban area  were high   incidence of infection in  both 2010 and 2015 in contrast  with rural area  , was  85(52.82% ) in urban  and 62(42.17%) in rural area in 2010 ,   with 207 (51.1%) in urban area and 198 ( 48.9%) in rural areas in 2015.Keywords: TB, Seroprevelance, Diyala province, Iraq.